Determinantes macroeconômicos da estrutura a termo da taxa de juros na América Latina - Andrade, Bruno Ferraz de (2016)
The paper proposes a three-factor model based on Huse (2007) methodology to relate observable macroeconomic and financial variables with the term structure of interest rates in Latin America (Brazil, Chile, Colombia and Mexico). We control for inflation rate, activity growth rate, exchange rate variation, credit default swaps (CDS), unemployment rate, and nominal interest rates as well as global factors such as the slope of the US yield curve and changes in commodity prices. The models explain more than 75% of the movements in the term structure of interest rates of Brazil, Chile and Colombia and 65% of Mexico. Positive changes in real activity and in inflation result in increases in the term structure. With exception to Chile, a rise in CDS leads to increases in the long-term interest rates. Increases in the unemployment rate have different effects on countries. In sum, exchange rate depreciations do not lead to increases in interest rates. This is probably due to central banks considering the effect of exchange rate depreciation on inflation to be transitory. In Mexico, interest rates also increase with the energy and metal prices. Brazilian energy prices are regulated, so it is not surprising that they do not have any impact on interest rates. Positive changes in the slope of the US yield curve affect similarly the slope of the yield curves in Latin America, reducing the short rates at the same time they increase long rates.